2018
DOI: 10.1177/1463949118774908
|View full text |Cite
|
Sign up to set email alerts
|

Preschool teachers as undercover agents within the figured world of public school

Abstract: This article explores the lived and sometimes clandestine professional experiences of early childhood teachers who exist within contexts where dominant discourses of professional are competing with teacher’s own understandings of their professional identities. Cultural models theory is used to shed light on the secrete and undercover work of public preschool teachers as they resist the prevailing managerial discourse and assert their understandings of their professional identities behind the closed doors of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Prior scholarship has conceptualized this new way of working as "border-crossing," which emphasizes school-based pre-K teachers' daily movements between the worlds of ECE and K-12 (Sumsion & Britt, 2003). Along these lines, research has demonstrated how toggling between ECE and K-12 practices creates dissonance for school-based pre-K teachers (Delaney, 2015(Delaney, , 2018Sisson, 2018). Other research has highlighted the challenges that policy actors face in bringing ECE and K-12 together in public pre-K (Brown, 2009;Brown & Gasko, 2012).…”
Section: The Pre-k Borderlandmentioning
confidence: 99%
“…Prior scholarship has conceptualized this new way of working as "border-crossing," which emphasizes school-based pre-K teachers' daily movements between the worlds of ECE and K-12 (Sumsion & Britt, 2003). Along these lines, research has demonstrated how toggling between ECE and K-12 practices creates dissonance for school-based pre-K teachers (Delaney, 2015(Delaney, , 2018Sisson, 2018). Other research has highlighted the challenges that policy actors face in bringing ECE and K-12 together in public pre-K (Brown, 2009;Brown & Gasko, 2012).…”
Section: The Pre-k Borderlandmentioning
confidence: 99%
“…By increasingly regulating teachers’ work, such policies limit teachers’ ability to use their professional judgement in decision making (Hatch, 2002: 459). A significant body of literature points to how discourses of “the professional” embedded in policy inform the ways teachers understand themselves as professionals (Bown and Sumsion, 2007; Bradbury, 2012; Delaney, 2015; Sisson, 2018; Sisson and Iverson, 2014; Woodrow, 2007). As teachers negotiate the range of discourses “through which they are shaped and in which they are positioned,” their subjectivities or “ways of being” are shaped (Osgood, 2006b: 7).…”
Section: The Politics Of Professionalizationmentioning
confidence: 99%